THE USE OF STORYTELLING TECNIQUE TO IMPROVE STUDENTS SPEAKING SKILL AT SMA NEGERI 5 KOTA TERNATE - Sucimulya Sucimulya Capalulu; Fitria Wulan Sari; Sri Ayu Budi Lestari (Jurnal Bilingual, 2024)
This research aims to find out whether the use of storytelling techniques significantly improves students' speaking skills at SMA Negeri 5 Ternate City. This research uses quantitative methods with a pre-experimental design. This research involved 20 students as samples. Storytelling is used as a teaching technique. The research results show that the use of storytelling techniques can significantly improve students' speaking comprehension. The research results showed that the students' average score on the post-test was higher (73.05) compared to the pre-test score (46.35). The t-test shows that the t-statistic value (4.35) exceeds the table value (2.11) at a significance level of 0.05 and 20 degrees of freedom using a one-sided test. Therefore, the null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that the storytelling technique is useful for improving students' speaking abilities.